Imaging of the Pediatric Knee - Yaya-Quezada, Carlos; Fanney, Lewis; Patel, Vandan; Taragin, Benjamin H.; Williams, Brendan A.; Simoni, Paolo; Nguyen, Jie C. (Seminars in Musculoskeletal Radiology, 2024)
During normal development, imaging findings in the immature knee joint may mimic pathology or indicate transient sites of weakness, prone to injury. This article reviews the development of the knee joint, age- and maturation-dependent imaging considerations, and various developmental variants that can be encountered, subdivided into those that involve the tibiofemoral and patellofemoral compartments, soft tissues, and osseous components. The tibiofemoral compartment section reviews the focal periphyseal edema zone (FOPE), ossification variants of the femoral condyles, distal femoral metaphyseal cortical irregularity from periosteal traction, and the metaphyseal subperiosteal stripe, which should be distinguished from pathologic mimickers such as endochondral ossification dysfunction, osteochondritis dissecans (OCD), fibroosseous lesion, periosteal and subcortical pathologies. The patellofemoral compartment section includes a review of partite patella, dorsolateral defect, variant trochlear morphology, and maturation-dependent sites of transient weakness that are prone to injury from repetitive overuse (Sinding-Larsen-Johansson syndrome and Osgood-Schlatter disease) and avulsion fractures (patellar sleeve and tibial tubercle avulsions). Finally, soft tissue (discoid lateral meniscus, meniscal flounce, anterior cruciate ligament variants) and osseous components (meniscal ossicle, fabella, and cyamella) are reviewed.
Keywords: fracture; normal variants; imaging; knee; growth plate